Histopathology Intestines of Trichogaster trichopterus Pall Infected by Digenean Trematode Parasites (Clinostomum sp.) - Panggabean, Devi Yunita; Riauwaty, Morina; Syawal, Henni (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2025)
Trichogaster trichopterus Pall is a freshwater fish widely found in Indonesian waters, particularly in the swamp areas of Riau Province. This study was conducted from September 2024 to March 2025 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine Science, University of Riau. The objective of this research was to analyze the intestinal tissue structure of T. trichopterus infected with Clinostomum sp. The methods used were purposive sampling and survey techniques. Fish samples were collected from the reservoir at the Faculty of Fisheries and Marine Science, University of Riau. Sampling was conducted three times over 30 days at four predetermined stations. Station I was located at the reservoir entrance, Station II to the west, Station III to the north of the entrance, with a 50-meter distance between stations, and Station IV was located upstream. The research procedures included sampling, intestinal organ fixation in formalin, and preparation of histopathological slides through a series of stages: dehydration, alcohol removal, infiltration, embedding, sectioning, staining, and mounting. Observed parameters included clinical symptoms and intestinal histological structure, which were analyzed descriptively. The results showed that the intestines of infected fish exhibited alterations, including epithelial lifting, goblet cell proliferation, oedema, hypertrophy, haemorrhage, inflammatory cell infiltration, and necrosis. The histopathological index of infected fish intestines reached a damage score of 7, categorised as severe. Based on the findings, it can be concluded that Clinostomum sp. infection causes significant alterations to the intestinal structure of T. trichopterus